Effects of the Enhanced Nurse Licensure Compact on Interstate Mobility and Nursing Employment - Hong-Lun Tiunn; Qian “Eric” Luo; Jordan Herring; Patricia Pittman (Health Affairs Scholar, 2026)
Abstract Background The U.S. continues to face persistent nursing shortages, even as many licensed nurses are not employed in nursing roles. The enhanced Nurse Licensure Compact (NLC 2.0), a mutual licensure recognition agreement, is promoted as a strategy to increase workforce supply and flexibility, yet no prior research has assessed whether it helps licensed but non-practicing nurses return to the profession. Methods Using American Community Survey data (2010–2023) and state-level licensure and employment data (2015–2023), we evaluated whether NLC 2.0 adoption is associated with changes in interstate RN inflows and in the license-employment mismatch—the share of active licenses not linked to payroll nursing employment—across 26 states. Results We found no statistically significant effect on interstate migration (+0.27 percentage points; p=0.67). However, adoption was associated with a 3.30-percentage-point reduction in the share of licensed nurses not employed in nursing (p=0.054), with the effect strengthening over time. A staggered difference-in-differences robustness check confirmed this pattern. Conclusions These findings suggest that while the compact does not draw nurses across state lines, it is associated with more licensed nurses working in nursing within adopting states. Licensure reform may therefore be one component of a broader strategy to support nurses’ return to bedside roles.